STUDY ON THE MANAGEMENT AND APPLICATION TEMPLATE INFORMATION TECHNOLOGY-BASED FINANCIAL STATEMENTS FOR SMALL AND MEDIUM BUSINESS (Case Study in Service Sector SMEs in Yogyakarta Special Region) - Sunarti, Katarina; Setyawan, Dr. Aris Budi (Accounting, 2009)
So far, small and medium enterprises (SMEs) is one of the business sector which contributes a high against the Indonesian economy but it is unfortunate when the low access to capital from the banking sector, restricting the development of its business due to the mastery of accounting and information technology access that is equipped with a variety of accounting applications still minimal. This study aimed to determine the profile of the financial management of SMEs, then the characteristics contained in the profile of financial management is taken into consideration in making the financial report templates based on Microsoft Excel 2007. This study is based on data collected from the SME Sector Services in Yogyakarta Special Region included in Category C (Real Estate, Renting and Business Services), Category O (Social Services, Sosbud, Entertainment, and Personal), Category I (Transport, Storage , and Communication), and other services in the Standard Industrial Classification in Indonesia. Data were analyzed through descriptive statistics of frequencies and percentages. Results of analysis regarding the financial management profile service sector SMEs in Yogyakarta Special Region is as follows: Transactions that often happens is that the sale transaction services in cash. Most of the SMEs sector, services have used the evidence of transactions in its business. Recording of transactions have been applied SME services sector to record financial transactions, which form the most frequently practiced record is the record and out of cash. Although many SMEs that keep records of financial transactions but the majority of service sector SMEs have not created the periodic financial reports. In connection with the implementation of financial report templates based on Microsoft Excel, both the SME sector, which has involved a computer services business as well as SMEs in the services sector that have not been using computers a majority willing to use the financial report templates based on Microsoft Excel 2007 to prepare its financial statements. With the template profile keuangam the financial statements must be in the form of a simple design for easy use. Simple concept is translated through the journals that consist only of a general journal that includes providing a column for the archiving of the transaction. With this template all financial reports to be automatically available to users. The process of testing this template on SME financial statements beauty salon